Prognostic value of heart rate deceleration capacity for functional outcomes in acute ischemic stroke: a prospective study - Zhou, Huizhong; Zhong, Jiaqi; Deng, Changman; Wang, Xingde; Xu, Yanhong; Yang, Jiajun (Frontiers in Endocrinology, 2025)
PurposeAcute ischemic stroke (AIS) is a leading cause of disability and mortality, with poor functional outcomes often linked to autonomic dysfunction. Deceleration capacity (DC), a marker of vagal activity, has been shown to predict cardiovascular outcomes, but its prognostic value in AIS remains underexplored. This study investigates the role of DC in predicting stroke recovery at 2 weeks and 3 months post-stroke.Patients and methodsThis prospective study included 423 AIS patients treated at a single center between January 2022 and December 2023. Cardiac autonomic function was assessed using DC and heart rate variability (HRV) parameters (SDNN, SDANN, RMSSD), derived from 24-hour Holter ECG monitoring. Patients were categorized into two groups based on DC: DC > 4.5 ms and DC ≤ 4.5 ms. Functional outcomes were measured using the modified Rankin Scale (mRS) at 2 weeks and 3 months post-stroke. Logistic regression models and Restricted Cubic Splines (RCS) were used to analyze the relationship between DC and stroke outcomes.ResultsPatients with lower DC (≤4.5ms) had significantly worse functional outcomes, as indicated by higher mRS scores at both 2 weeks and 3 months. The DC ≤ 4.5 ms group also had a higher prevalence of comorbidities such as diabetes and hypertension. RCS analysis revealed a non-linear relationship between DC and stroke outcomes, with a significant threshold at DC = 4.5 ms. The 3-month outcome model, including age and DC, demonstrated strong predictive ability with an AUC of 0.744.ConclusionsThis study highlights the importance of DC as a prognostic marker for short-term stroke recovery. Lower DC values are associated with worse outcomes, suggesting that DC may serve as an early predictor of stroke prognosis. Future research should focus on validating these findings in larger, multicenter cohorts and exploring interventions targeting autonomic dysfunction to improve stroke recovery.